Radiation hardness of polysiloxane-based scintillators - Zhmurin, P.М.; Yelisieiev, D.A.; Alekseev, V.D.; Yelisieieva, O.V.; Нurkalenko, Yu.О.; Popov, V.Ph. (Вопросы атомной науки и техники, 2022)
Polysiloxane-based scintillators with different contant of aromatic chromophore groups have been obtained. 2,5-diphenyloxazole and its alkyl derivative were used as activators. The optical and scintillation properties of the obtained polysiloxane scintillators have been studied, and their radiation resistance has been determined. The prospect of using the material in fields with high dose loads is estimated. Отримано сцинтилятори на полісилоксанових основах, що містять у своєму складі різну кількість ароматичних хромофорних груп. Як активатори використано 2,5-дифенілоксазол і його алкілпохідне. Вивчено оптичні та сцинтиляційні властивості отриманих полісилоксанових сцинтиляторів, визначена їх радіаційна стійкість. Оцінено перспективу використання матеріалу в полях з великими дозовими навантаженнями. Получены сцинтилляторы на полисилоксановых основах, содержащих в своем составе разное количество ароматических хромофорных групп. В качестве активаторов использовано 2,5-дифенилоксазол и его алкилпроизводное. Изучены оптические и сцинтилляционные свойства полученных полисилоксановых сцинтилляторов, определена их радиационная стойкость. Оценена перспектива использования материала в полях с большими дозовыми нагрузками.